Borderline Personality Disorder Symptoms and Newlyweds’ Observed Communication, Partner Characteristics, and Longitudinal Marital Outcomes - Lavner, Justin A. (J Abnorm Psychol, 2015)
Given borderline personality disorder (BPD)’s relation with interpersonal dysfunction, there is substantial interest in understanding BPD’s effect on marriage. The current study used data from a community sample of 172 newlywed couples to examine spouses’ BPD symptoms in relation to their observed communication, partner BPD symptoms, 4-year marital quality trajectories, and 10-year divorce rates. BPD symptoms were correlated cross-sectionally with more negative skills during observational problem-solving and social support tasks, and spouses reporting more BPD symptoms were married to partners reporting more BPD symptoms. Longitudinally, hierarchical linear modeling of newlyweds’ 4-year marital trajectories indicated that BPD symptoms predicted the intercept of marital quality for spouses and their partners, reflecting lower levels of marital satisfaction and higher levels of marital problems. BPD symptoms did not predict 10-year divorce rates. These findings highlight the chronic relationship impairment associated with BPD symptoms, indicate that distress begins early in marriage, and suggest that partners with higher levels of BPD symptoms remain in more troubled marriages.